Consommation d`oxygène chez des cyclistes confirmés lors d`une séance composée d`intervalles courts (30 s/30 s) sur bicyclette ergométrique - El Hage,Z.; El Hage, R.; Moussa, E.; Jacob, C. (Science & Sports, 2012)
Introduction: Intermittent training like 30 s/30 s is an effective method used by many athletes and team sports specialists to enhance maximum oxygen consumption. However, few studies aimed at exploring the effectiveness of this type of training on the maximal oxygen uptake (VO2max) in cyclists. The aim of this study was to investigate whether an intermittent training (30 s/30 s) realised at the maximum aerobic power (MAP) and with a passive recovery permits to attain maximum oxygen uptake in well-trained cyclists. Methods and results: Seven trained cyclists participated in this study. During a preliminary visit, the maximum oxygen uptake (VO2max) of each subject was determined using a continuous incremental test on an ergocycle. VO2max was measured using an automated breath by breath system. After one week, the subjects performed 20 repetitions of 30 s cycling at maximum aerobic power alternated with 30 s passive recovery. None of the cyclists reached more than 90% of VO2max. Conclusion: The intermittent training method 30 s/30 s realised using 100% of MAP and a passive recovery does not permit to reach 90% of maximum oxygen consumption in well-trained cyclists.